In-silico analysis of PtpA - an antigenic protein of Mycobacterium tuberculosis - P, Merly D; S, Anil Kumar; Mohan Reddy, K; B, Tejaswini; P, Darley S; Sulochana, M B (Recent Research in Science and Technology, 2012)
PtpA, a low-molecular weight tyrosine phosphatase, is a secreted protein of Mycobacterium tuberculosis (Mtb). Many secretory proteins of Mtb are known to be the prominent targets of host immune response. It plays an important role in host-pathogen interaction and it interferes with the passing of the protein from one endosomal vesicle to the next endosomal vesicle in the infected macrophage. It inhibits host phagolysosomal fusion in the infected macrophages and thus allows the bacteria to survive within macrophages. Analysis of primary and secondary structure of the protein was done by ProtParam and GOR IV respectively. Since the number of negatively charged residues are higher than the positively charged residues, PtpA is an acidic protein. Immunity against Mtb is T-cell mediated Thus an important criterion in seeking protective antigens should be that they induce T-cell- mediated immunity. The characterization of PtpA inducing CD4+ T-cell responses could critically contribute to the development of subunit vaccines for Mtb. Here we performed computational analysis by using Proped, T-cell epitope prediction program. In-silico antigenicity prediction of PtpA was done using VaxiJen. Owing to the resistance of this protein to the natural immune response, in-silico antigenicity and T-cell epitope prediction will be helpful to design better subunit vaccines to develop effective acquired immune response to Mtb.